Saraca asoca Bark-derived Procyanidins Mitigate Doxorubicin-induced Cardiotoxicity - Vemuri, Praveen Kumar (Asian Journal of Pharmaceutics (AJP), 2024)
Background: Doxorubicin (DOX) is a commonly utilized chemotherapeutic agent for treating hematological malignancies and solid tumors. However, its widespread use is hindered by the significant side effect of oxidative injury-related cardiotoxicity. Objective: This study explores the potential of procyanidins (PCNs) derived from Saraca asoca bark, known for its robust free radical scavenging properties, in preventing DOXinduced cardiotoxicity in rats. Materials and Methods: Rats were treated intraperitoneally with a cumulative dose of 15 mg/kg DOX, both with and without prior administration of PCNs. Results: The findings revealed that DOX caused cardiac dysfunction, myocardial injury, and increased oxidative stress in cardiac tissues. The cardiac impairment included increased QT-interval and ST-interval in electrocardiograph (ECG) and reduced left ventricular developed pressure. DOX-induced myocardial injury manifested as elevated levels of creatine kinase, alanine aminotransferase, and aspartate aminotransferase in serum, along with observable myocardial lesions. Pretreatment with PCNs at a dosage of 150 mg/kg daily effectively mitigated DOX’s adverse effects, such as myocardial injury and impaired heart function. PCN pretreatment ameliorated cytoplasmic vacuolization, increased left ventricular developed pressure, and improved ECG parameters. The cardioprotective impact of PCNs correlated with reduced lipid peroxidation and enhanced cardiac antioxidant capacity in DOX-treated rats also administered PCN. In addition, an in vitro cytotoxic study demonstrated that PCNs did not compromise DOX’s antineoplastic activity against A549 adenocarcinoma cells. Conclusion: Collectively, these findings indicate that PCNs shield cardiomyocytes from DOX-induced cardiotoxicity by suppressing oxidative stress.